Echoes : painterly repetitions and revisions in an age of digitally mediated images - Aikman, Jake (Michaelis School of Fine Art, 2024)
The mediation of landscape in painting is explored by looking at a specific case in the Romantic tradition (Caspar David Friedrich) in relation to contemporary painting, which highlights a shift from a view of a utopian unmediated landscape to our present reconfigurations of fragmented past, sourced from mediated images. In section two a theoretical and historical context for situating my practice is discussed. Examples of repetition from early Modernism through to the Pop Art movement highlight the differences and similarities of my intentions in the practical work. In addition, the thematic component of the project is discussed specifically with regard to the prevalence of affinities with the thematic interests from the movement referred to as Romanticism. For the purposes of explicating an historical framing of my project, the focus on Romanticism is restricted to the paintings of Caspar David Friedrich as apposed to providing a survey of an entire movement. The return of romantic themes in my own practice and within a broader contemporary practice is argued to be another form of repetition, thus expanding the scope of repetition rather than dividing the project into separate components. Section three discusses contemporary examples of artists who have influenced my research project and specific works relating to the topic of repetition are examined. This section also links the earlier discussion of Friedrich's romantic painting with contemporary artists, namely Peter Doig and Christopher Orr, associated with the current ressurgence of artists adopting and adapting the spirit and thematic concerns of Romanticism in contemporary practice. Section four examines the methodology and process of my research project. I start by framing the context for the practical processes employed and how they developed. I discuss how, through the process of implicating these methods, a dialogue between technical strategy and content arose. Section five illustrates and provides a detailed discussion of the individual works produced for the exhibition.